Tumor start‐up: mitochondrial fusion makes it happen - Rebelo, Ana R (EMBO J, 2020)
Whether changes in cellular metabolism precede tumor formation and trigger malignant properties or simply serve as a bioenergetic adaptation of cancer during disease progression remains debated. Bonnay et al (2020) now show that a metabolic reprogramming toward increased oxidative phosphorylation is required for irreversible cell immortalization and subsequent tumor formation.